Improvement of Strength and Volume-Change Properties of Expansive Clays with Geopolymer Treatment. Issue 9 (September 2021) - Samuel, Rinu; Puppala, Anand J.; Banerjee, Aritra; Huang, Oscar; Radovic, Miladin; Chakraborty, Sayantan
Expansive soils are conventionally treated with chemical stabilizers manufactured by energy-intensive processes that significantly contribute to carbon dioxide emissions globally. Geopolymers, which are synthesized from industrial byproducts rich in aluminosilicates, are a viable alternative to conventional treatments, as they are eco-friendly and sustainable. In this study, a metakaolin-based geopolymer was synthesized, and its effects on the strength and volume-change behavior of two native expansive soils from Texas, with a plasticity index over 20 were investigated. This paper elaborates on the geopolymerization process, synthesis of the metakaolin-based geopolymer, specimen preparation, and geopolymer treatment of soils. Comprehensive material testing revealed two clays with a plasticity index over 20. They were each treated with three dosages of the metakaolin-based geopolymer and cured in 100% relative humidity for three different curing periods. The efficiency of geopolymer treatment was determined by testing the control and geopolymer-treated soils for unconfined compressive strength (UCS), one-dimensional swell, and linear shrinkage. Field emission scanning electron microscope (FESEM) imaging was performed on the synthesized geopolymer, as well as on the control and geopolymer-treated soils, to detect microstructural changes caused by geopolymerization. A significant increase in UCS and reduction in swelling and shrinkage were observed for both geopolymer-treated soils, within a curing period of only 7 days. The FESEM imaging provided new insights on the structure of geopolymers and evidence of geopolymer formation in treated soils. In conclusion, the metakaolin-based geopolymer has strong potential as a lower-carbon-footprint alternative to conventional stabilizers for expansive soils.